1994
DOI: 10.1111/j.1528-1157.1994.tb02924.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Phenytoin‐Induced Congenital Malformations by Coadministration of the Antiepileptic Drug Stiripentol in a Mouse Model

Abstract: To test the hypothesis that the cytochrome P-450-inhibiting antiepileptic drug (AED) stiripentol (STP) can reduce the incidence of phenytoin (PHT) induced congenital malformations, we chronically administered the AEDs to three inbred mouse strains. The frequency of congenital defects in PHT-treated animals was dosage dependent, ranging from 7 to 55%. When STP was coadministered orally with PHT, there was a significant reduction in fetal defects in SWV and C57BL/6J mouse strains. A replication of the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 21 publications
(18 reference statements)
0
7
0
3
Order By: Relevance
“…PHT is metabolized in the liver through cytochrome P450 enzymes, and in studies in which cytochrome P450 inhibitors were employed, the incidence of PHT-induced dysmorphogenesis was significantly reduced (Finnell et al 1994(Finnell et al , 1999. Green tea catechins (namely EGCG) have been found to inhibit some cytochrome P450 enzymes (Muto et al 2001).…”
Section: Discussionmentioning
confidence: 98%
“…PHT is metabolized in the liver through cytochrome P450 enzymes, and in studies in which cytochrome P450 inhibitors were employed, the incidence of PHT-induced dysmorphogenesis was significantly reduced (Finnell et al 1994(Finnell et al , 1999. Green tea catechins (namely EGCG) have been found to inhibit some cytochrome P450 enzymes (Muto et al 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Oksidativ metabolisering av antiepileptika er saerlig avhengig av cytochrom P450 isoenzymer som derved regulerer omsetningen av antiepileptika, men også produksjonen av bioaktive metabolitter som kan ha skadelige, evt. teratogene effekter (45)(46)(47)(48). Genetisk betingende forskjeller i cytochrom P450 isoenzym aktivitet kan forklare individuelle forskjeller i omsetning av enkelte antiepileptika og interaksjoner mellom antiepileptika.…”
Section: Teorier Om åRsaker Til Fosterskaderunclassified
“…Genetisk betingende forskjeller i cytochrom P450 isoenzym aktivitet kan forklare individuelle forskjeller i omsetning av enkelte antiepileptika og interaksjoner mellom antiepileptika. De kan også meget vel medvirke til genetiske forskjeller i teratogent potensiale av enkelte antiepileptika (45)(46)(47)(48). Stiripentol, et antiepileptikum som hemmer cytochrom P450, reduserer f.eks.…”
Section: Teorier Om åRsaker Til Fosterskaderunclassified
See 1 more Smart Citation
“…Finnell et al (1994) demonstrated a significant reduction of the teratogenic effect of phenytoin in mice by the co-administration of stiripentol, an effect that could be explained in terms of reduced production of a teratogenic metabolite of phenytoin (473).…”
Section: Stiripentolmentioning
confidence: 99%